Construction of Islamic Identity in Organizational Documents: A Study of Primary Sources on the Articles of Association of Islamic Organizations in Indonesia - Mukafi, Ahmad; Marjani, Muhammad Yusuf (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to examine the construction of Islamic identity within the Articles of Association and Bylaws (AD/ART) of Islamic mass organizations (Ormas) in Indonesia, focusing on three major organizations: Nahdlatul Ulama (NU), Muhammadiyah, and Lembaga Dakwah Islam Indonesia (LDII). Each of these organizations plays a significant role in Indonesia’s socio-religious dynamics, and their AD/ART documents function as operational foundations while reflecting the core values upheld by the organizations. This research employs a qualitative method using a document analysis approach, with the AD/ART documents serving as primary sources, to explore how Islamic identity is constructed and articulated within organizational regulations. The main focus of this study is to understand how each Islamic organization formulates its perspective on Islam within its organizational structure and governing rules, and how this formulation influences their social interactions and positions within Indonesian society. The expected findings of this study include the identification of both differences and similarities in the construction of Islamic identity among NU, Muhammadiyah, and LDII, as well as their respective contributions to the dynamics of Islam in Indonesia across social, political, and cultural dimensions. This research is expected to contribute to a deeper understanding of the role of Islamic mass organiations in shaping Islamic identity and their broader influence on society.